Finance and Development, December 1998. - International Monetary Fund. External Relations Dept. (Washington, D.C. : International Monetary Fund, 1998)
How will EMU affect the way the IMF monitors economic developments in its European members?.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet